In vitro Assessment of Antiviral Activity of Cold Atmospheric Pressure Plasma Jet against the Human Immunodeficiency Virus (HIV) - Mohammad Reza Amiran; Abbas Akhavan Sepahi; Rezvan Zabiollahi; Hamid Ghomi; Seyed Bahman Momen; Mohammad Reza Aghasadeghi (Pasteur Institute of Iran, 2016)
Introduction: The human immunodeficiency virus (HIV) is a threat to global health and the need for finding new methods of antivirus research, in particular against HIV has increased in recent years. In this study, we investigated the ability of the cold atmospheric pressure plasma jet (CAPPJ) using helium to inhibit the replication of HIV virions. Methods: Single cycle replicable HIV (SCR-HIV) virions were produced by transfection of HEK293T cells with pmzNL4-3, pSPAX.2, and pMD2.G plasmids. The HeLa immortal cell line was infected with the virus SCR-HIV and then irradiated by CAPPJ at different voltages and times. The amount of the P24 antigen inside cell supernatant was measured by an ELISA method. Moreover, the cytotoxicity of this plasma jet and the viability of cells were evaluated by the XTT method. Results: The inhibition of HIV by CAPPJ increased with increasing of voltage and the time of radiation. The highest voltage of 12 kv at 240 s caused virus inhibition; however, the cytotoxicity of HeLa cell line also elevated with increasing of voltage and time. Conclusion: CAPPJ substantially suppresses HIV infection in vitro while causing toxicity for HeLa cell line